2008
DOI: 10.1158/1078-0432.ccr-08-0666
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid Markedly Improves Bone Mineral Density for Patients with Monoclonal Gammopathy of Undetermined Significance and Bone Loss

Abstract: Purpose: Patients with monoclonal gammopathy of undetermined significance (MGUS) have increased rates of bone resorption, osteopenia, osteoporosis, and risk of fractures. This study was undertaken to determine the efficacy and safety of zoledronic acid for patients with MGUS and enhanced bone loss. Experimental Design: In this phase II open-label study, 54 patients with MGUS and osteopenia or osteoporosis were administered zoledronic acid 4 mg i.v. at 0, 6, and 12 months. The primary efficacy end point was bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 29 publications
0
42
0
1
Order By: Relevance
“…34 Therefore, avoiding events associated with significant morbidity and mortality-such as fractures-is of paramount importance for patients with MGUS. In 2 studies of short duration, both alendronate 35 and zoledronic acid 36 were shown to increase aBMD in MGUS patients after 18 and 13 months, respectively. Although both bisphosphonates would be expected to decrease fracture risk based on this documented increase in aBMD, this has not yet been demonstrated in randomized trials.…”
Section: Discussionmentioning
confidence: 98%
“…34 Therefore, avoiding events associated with significant morbidity and mortality-such as fractures-is of paramount importance for patients with MGUS. In 2 studies of short duration, both alendronate 35 and zoledronic acid 36 were shown to increase aBMD in MGUS patients after 18 and 13 months, respectively. Although both bisphosphonates would be expected to decrease fracture risk based on this documented increase in aBMD, this has not yet been demonstrated in randomized trials.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment with bisphosphonates has been investigated to some extent in MGUS, and has been shown to increase BMD. 36,37 However, the effect of bisphosphonates on future skeletal-related events and bone structure in MGUS remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, 2 studies have evaluated the effect of bisphosphonates in patients with MGUS and have found an improvement in bone mineral density and bone loss. 20,21 Randomized clinical trials are needed to establish the role of bisphosphonates in patients with MGUS.…”
Section: Org Frommentioning
confidence: 99%